2022
DOI: 10.1002/cncr.34252
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and risk of breast cancer: A cohort study and Mendelian randomization analysis

Abstract: BACKGROUND Estrogen is involved in both bone metabolism and breast cancer proliferation. However, evidence about the risk of breast cancer according to women's bone mineral density (BMD) is scarce, and little is known about their causal associations. METHODS Women participating in the UK Biobank cohort were used to investigate the association between BMD and the risk of breast cancer using Cox regression models. Instrumental variants associated with estimated BMD (eBMD) were extracted from genome‐wide associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(96 reference statements)
0
3
2
Order By: Relevance
“…A prior MR analysis in European populations revealed no genetic evidence supporting a causal link between BMD and BC risk. The observed association between the two was explained by the pleiotropic effects of genetic variants [45]. This is inconsistent with the results of our MR analysis, and ethnic differences may be the primary reason for the discrepancy between this study and the MR analysis on European populations.…”
Section: Discussioncontrasting
confidence: 99%
“…A prior MR analysis in European populations revealed no genetic evidence supporting a causal link between BMD and BC risk. The observed association between the two was explained by the pleiotropic effects of genetic variants [45]. This is inconsistent with the results of our MR analysis, and ethnic differences may be the primary reason for the discrepancy between this study and the MR analysis on European populations.…”
Section: Discussioncontrasting
confidence: 99%
“…The same results are consistent with a recently published Mendelian Randomized study of bone density and breast cancer risk. The results of this study also provide no evidence to support a causal association between BMD and breast cancer, while considering that the association found in observational studies could be explained by polymorphic genetic variants that contribute to the pathology of osteoporosis and breast cancer 41 . Elevated hormone levels, including levels of oestradiol and testosterone, have been found to be associated with BMD and breast cancer in several studies 15 , 42 .…”
Section: Discussioncontrasting
confidence: 88%
“…Estrogens are important for bone metabolism via a variety of mechanisms in osteoblasts, osteocytes, osteoclasts, immune cells, and other cells to maintain bone mineral density ( Khalid and Krum, 2016 ). Lots of research reporter that estrogen receptor gene ESR1 polymorphisms are associated with BMD and osteoporosis in humans and mice ( Trajanoska et al, 2018 ; Zhang et al, 2022 ). Faccio et al identified that Vav3 , a Rho family guanine nucleotide exchange factor, as essential for stimulated osteoclast activation and bone density in vivo ( Faccio, et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%